Without access to social media platform data we risk being left in the dark - Parry, Douglas (My University, 2023)
Social media data are essential for studying human behaviour and understanding potential systemic risks. Social media platforms have, however, begun to remove access to this data. In response, other countries and regions have implemented legislation that compels platforms to provide researchers with data access. In South Africa, we have lagged behind the Global North when it comes to using platform data in our research and, given the recent access restrictions, we risk being left behind. In this commentary, I call attention to this critical issue and initiate a conversation about access to social media data in South Africa.
Keywords: API; data access; digital services act; digital trace data; dsa; social media